2020
DOI: 10.1055/a-1261-3103
|View full text |Cite
|
Sign up to set email alerts
|

Stenting to prevent esophageal stricture after circumferential endoscopic submucosal dissection: an experimental study

Abstract: Background and study aims Circular ESD (CESD) is a treatment option for patients with extensive early esophageal cancer. Its major drawback is the development of a stricture. Stenting may represent an attractive prevention strategy. We designed an experimental study to assess the effect of stents covered with acellular biomatrix (AB) and a drug-eluting stent. Materials and methods Thirty-five 35 pigs underwent CESD and were randomized into six groups: G1 (control), G2 (SEMS), G3 (SEMS + AB), G4 (SEMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ezoe et al reported that balloon dilation reduces the overall stricture rate, but 52% of patients in their study still had strictures [12]. A study of a porcine esophageal circular ESD model found that stent implantation did not prevent esophageal strictures [2]. Oral steroids are a relatively effective approach in preventing post-ESD stricture if the resection range is less than 100% of the esophageal circumference, and can reduce the severity of stricture and the number of dilations required [13].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ezoe et al reported that balloon dilation reduces the overall stricture rate, but 52% of patients in their study still had strictures [12]. A study of a porcine esophageal circular ESD model found that stent implantation did not prevent esophageal strictures [2]. Oral steroids are a relatively effective approach in preventing post-ESD stricture if the resection range is less than 100% of the esophageal circumference, and can reduce the severity of stricture and the number of dilations required [13].…”
Section: Discussionmentioning
confidence: 97%
“…Esophageal strictures are noted in 40%, 57%, and 100% of grade IIb, IIIa, and IIIb burns, respectively [11]. In contrast, ESD of greater than three-fourths of the luminal circumference results in strictures in 70-80% of cases; the rate is almost 100% in patients who undergo circular resection [2]. When the strictures are longer (> 2 cm), angulated, irregular, and severely narrowed, the treatment proves particularly difficult; and the strictures frequently become recurrent or refractory to treatment [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation